1997
DOI: 10.1073/pnas.94.13.6658
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc transactivation of LDH-A : Implications for tumor metabolism and growth

Abstract: Cancer cells are able to overproduce lactic acid aerobically, whereas normal cells undergo anaerobic glycolysis only when deprived of oxygen. Tumor aerobic glycolysis was recognized about seven decades ago; however, its molecular basis has remained elusive. The lactate dehydrogenase-A gene (LDH-A), whose product participates in normal anaerobic glycolysis and is frequently increased in human cancers, was identified as a c-Myc-responsive gene. Stably transfected Rat1a fibroblasts that overexpress LDH-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
716
1
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 956 publications
(776 citation statements)
references
References 67 publications
33
716
1
6
Order By: Relevance
“…Neoplastic cells accomplish the consumption of the surplus pyruvate generated by glycolysis, which is not fed into the TCA cycle, also by conversion into lactate by lactate dehydrogenase (LDH)-A (Shim et al, 1997) and by fueling it into lipid biosynthesis . Removal of this excess of pyruvate molecules is crucial to avoid pyruvate-induced apoptosis (Thangaraju et al, 2006).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoplastic cells accomplish the consumption of the surplus pyruvate generated by glycolysis, which is not fed into the TCA cycle, also by conversion into lactate by lactate dehydrogenase (LDH)-A (Shim et al, 1997) and by fueling it into lipid biosynthesis . Removal of this excess of pyruvate molecules is crucial to avoid pyruvate-induced apoptosis (Thangaraju et al, 2006).…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…MYC activates glycolysis through transcriptional induction of various glycolytic enzymes and LDH-A (Shim et al, 1997;Kim et al, 2004). Recent experiments using double transgenic mice expressing c-MYC in a doxycycline-dependent manner specifically in hepatocytes revealed that overexpression of a multitude of glycolysis genes in tumors was abrogated by switching off c-MYC expression .…”
Section: The Metabolic Pattern Of Cancer Cellsmentioning
confidence: 99%
“…Although an inefficient mechanism for ATP generation, tumor cells become energy-independent from the mitochondrion, which also harbors many death-activating proteins, like GRIM-19. Previous studies have shown that the expression of lactate dehyrogenase (Shim et al, 1997) is directly controlled by the c-myc oncogene, whose expression in turn is regulated by STAT3. In fact, a number of studies have shown an inactivation of enzymes involved in Kreb's cycle and a consequent dysfunction of oxidative phosphorylation in human tumors (Pollard et al, 2003(Pollard et al, , 2005Morris et al, 2004).…”
Section: Inactivation Of Grim-19 In Cancer I Alchanati Et Almentioning
confidence: 99%
“…The metabolic enzyme lactate dehydrogenase A (Ldh-A) is a c-Myc target gene recently shown to sensitize cells to a novel glucose-dependent apoptotic pathway (Shim et al, 1997(Shim et al, , 1998. Ldh-A is part of the normal anaerobic glycolysis pathway which operates at higher levels in hypoxic cells.…”
Section: Myc Target Genes and Apoptosismentioning
confidence: 99%
“…Notably, MCF7 breast carcinoma cells deprived of glucose exhibit both c-Myc elevation and signi®cant cell death, which can be blocked by the addition of antisense c-Myc oligonucleotides (Lee et al, 1997). The identi®cation of Ldh-A as a genetic target of c-Myc may provide a molecular basis for this e ect (Shim et al, 1997). Notably, when Rat1 cells overexpressing Ldh-A are deprived of glucose or are treated with the antimetabolite 2-deoxyglucose, they engage a p53-independent death program, whereas control cell lines merely respond by G0/G1 arrest (Shim et al, 1998).…”
Section: Myc Target Genes and Apoptosismentioning
confidence: 99%